Tamoxifen attenuates manganese-induced dysregulation of neuronal REST via the genomic ER-α mechanism - Digman, Alexis; Pajarillo, Edward; Kim, Sanghoon; Ajayi, Itunu; Son, Deok-Soo; Aschner, Michael; Lee, Eunsook (Frontiers in Molecular Neuroscience, 2025)
Chronic exposure to elevated levels of manganese (Mn) causes a neurological disorder referred to as manganism, resembling pathological symptoms of Parkinson’s disease (PD). The repressor element-1 silencing transcription factor (REST) induces neuroprotection in several neurological disorders, including PD and Mn toxicity. Tamoxifen (TX), a selective estrogen receptor modulator, has been shown to afford neuroprotective effects in various experimental models and increase REST expression via the non-genomic estrogen receptor (ER)/Wnt signaling in Cath. a-differentiated (CAD) neuronal cultures. The present study investigated whether TX enhances REST transcription through the genomic estrogen receptor (ER) pathway in CAD cells, using a combination of Western blotting, quantitative reverse transcription polymerase chain reaction (qRT-PCR), promoter activity assays, chromatin immunoprecipitation, electrophoretic mobility shift assays, and site-directed mutagenesis. The findings showed that the REST promoter sequences contained half-site estrogen response elements (ERE) motifs. The ER-α pathway primarily upregulated REST, as the ER-α selective agonist propylpyrazole triol (PPT) (1 μM) predominantly increased REST transcription and attenuated Mn (250 μM)-induced REST reduction in CAD cells. TX induced REST upregulation by activation of the genomic ER-α pathway, as it increased nuclear ER-α’s interaction with cyclic adenosine monophosphate (AMP) response element (CREB)-binding protein and Sp1 and promoted ER-α binding to the half-site ERE in the REST promoter. Moreover, the ERE mutation in the REST promoter reduced TX-induced REST promoter activity, and TX reversed Mn-induced REST transcriptional repression. Our novel findings suggest that the genomic ER-α pathway plays a critical role in TX-induced REST upregulation and mitigation of Mn-induced decreases in REST expression.